Leading libraries : how to create a service culture - VanDuinkerken, Wyoma; Kaspar, Wendi Arant (American Library Association, 2015)
This valuable resource gathers the principles and best practices of leadership, and points the way towards creating a service culture that makes every staff member a library leader.